Pengaruh kompensasi finansial dan kepuasan kerja terhadap organizational citizenship behavior (OCB) pada karyawan PT. Kilang Lima Gunung - Sulastri, Sulastri; Andriani, Chichi; Latifa, Suci Kurnia (Jurnal Kajian Manajemen Bisnis, 2018)
This study aims to determine the effect of Financial Compensation and Job Satisfaction of Organizational Citizenship Behavior (OCB) on Employees of PT. Kilang Lima Gunung. Population of this research is all employees at PT. Kilang Lima Gunung totaling 105 people. The sampling technique of this study is Cluster Random Sampling with a sample of 104 employees. The analysis technique used is path analysis. Data analysis in this study using Analysis of Moment Structure using IBM SPSS AMOS 22 program. The results showed that: (1) financial compensation did not positively and significantly affect the Organizational Citizenship Behavior (OCB) on the employees of PT. Gunung Lima refinery, (2) financial compensation has a positive and significant impact on employee work satisfaction of PT. Kilang Lima Gunung, (3) job satisfaction has a positive and significant impact on Organizational Citizenship Behavior (OCB) of PT. Kilang Lima Gunung, (4) financial compensation has significant effect to Organizational Citizenship Behavior (OCB) of PT.Kilang Lima Gunung through job satisfactionKeywords: Financial compensation; job satisfaction; organization citizenship behavior